Baitul Māl Wat Tamwīl (BMT) sebagai Alternatif Strategis Memajukan Usaha Mikro Kecil Sektor Pertanian - Atika Rukminastiti Masrifah (Islamic Economics Journal, 2017)
Micro and Small Enterprises (MSE’s) has an important role in economic development in Indonesia. However, MSE’s still has a lot of problem. They are still having difficulties to access business financing provided by Islamic financial institutions and banking. This paper attempts to analyze the benefit, opportunity, cost and risk of Islamic financial institutions espesially Baitul Mal wat Tamwil (BMT) in promoting MSE’s utilizing Analytical Network Process (ANP) method with Benefit Opportunity Cost Risk (BOCR) approach, including the proposed alternative strategies. Results of this study show that the highest priority of cost and risk is the lack of support and the understanding of community. Moreover the highest priority of benefit and opportunity is that Islamic Financial Institutions has a just profit-loss sharing system i.e., taking into account the possibility of profit and loss, and BMT has a wide and deep outreach for the poor and poorest. The priorities of strategic alternative in the agricultural sector to promote SME are providing alternative financing schemes based on sub-activities, establishing Linkage Program between BUS-BPRS-LKA-Government, organizing incentive schemes, and forming a National Agrarian Bank, which will be totally focused on projects in agriculture.